2020
DOI: 10.1177/1747493020908140
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of early urinary catheterization after acute stroke: Secondary analyses of the international HeadPoST trial

Abstract: Total Word Count: 4173 (Abstract 244; Main 2083) 2 Brief title: Urinary catheterization and stroke outcome Abstract Background: An indwelling urinary catheter (IUC) is often inserted to manage bladder dysfunction but its impact on prognosis is uncertain. We aimed to determine the association of IUC use on clinical outcomes after acute stroke in the international, multi-center, cluster crossover, Head Positioning in Acute Stroke Trial (HeadPoST). Methods: Data were analyzed on HeadPoST participants (n=11,093) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…"No instruction for IUC removal from physicians" was also recorded in 25 of the 56 days. Previous studies showed that IUC use is associated with poor functional outcomes and high mortality after acute stroke, [5][6][7] and suggested the need for further research on appropriate IUC use. 5,6 Few studies have reported on measures to reduce IUC use among stroke patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…"No instruction for IUC removal from physicians" was also recorded in 25 of the 56 days. Previous studies showed that IUC use is associated with poor functional outcomes and high mortality after acute stroke, [5][6][7] and suggested the need for further research on appropriate IUC use. 5,6 Few studies have reported on measures to reduce IUC use among stroke patients.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that IUC use is associated with poor functional outcomes and high mortality after acute stroke, [5][6][7] and suggested the need for further research on appropriate IUC use. 5,6 Few studies have reported on measures to reduce IUC use among stroke patients. In this regard, two previous studies in neuro-ICU are informative, albeit the use of a single centre, incremental and adaptive feedback design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is illustrated in this issue by secondary analysis of the HeadPoST trial. 5 This trial was designed to assess positioning following stroke. However, the authors also analyzed associations between an indwelling urinary catheter and outcome.…”
mentioning
confidence: 99%